Many factors of construction manufacture, which are negative influence on the state of environment - Tugai, O.; Osypova, A. (Ways to Improve Construction Efficiency, 2018)
The results of systematization of the initial set of factors of construction production, which have a negative impact on the environment, are described. Separated group of factors: emissions into soil; emissions to groundwater and surface waters; emissions into atmospheric air; biological effects; mechanical influences; physical effects. The significance of these groups of factors and their composition is established.